Sustaining development in the Commonwealth Caribbean: statement - Nicholls, Sir Neville (CDB BridgetownBB, 1993)
Posits that if the Commonwealth Caribbean is to achieve sustainable development, it must in addition to promoting efficiency in the traditional sectors, bring about a substantial change in outlook, in types of products and services produced, in its development and use of technology in the prevailing orthodoxy in the areas of education and training, and in several of the institutions through which our social and economic affairs are currently organised.